Rhizoremediation of phenol and chromium by the synergistic combination of a native bacterial strain and Brassica napus hairy roots - Ontañon, Ornella Mailén (2014)
A bacterial strain resistant to phenol and Cr (VI) was isolated from an industrial polluted soil of Córdoba province (Argentina), which was identified as Pantoea sp. FC 1. This microorganism was able to use phenol as sole carbon source. In addition it was capable of reducing Cr (VI) to Cr (III) in mineral and nutrient media. The isolated strain exhibited some properties as plant-growth promoting bacterium (PGPB), such as production of Indole Acetic Acid (IAA) and synthesis of siderophores, as well as being capable of solubilizing inorganic phosphates. A rhizoremediation system using the association Pantoea sp. FC 1-Brassica napus hairy roots (HRs) was tested for phenol and Cr (VI) removal in a hydroponic system. Microbial inoculation improved both phenol removal and chromium accumulation efficiency by HRs, showing a significant increase in Cr (III) accumulation compared to non-inoculated HRs, exceeding 1000 mg kg−1. Cr (III) was detected in HR biomass and supernatants, suggesting a possible Cr (VI) reducing activity of B. napus HRs. Basic studies in plant model systems, such as HRs, provide additional useful information that could facilitate the transition of this technology into plants suitable for practical rhizoremediation applications.